ANALYSIS OF THE INVENTORY GOODS SYSTEM SIBAPER IN IMPROVING THE EFFECTIVENESS OF FINANCIAL REPORT RECORDING AT THE SOCIAL SERVICES OFFICE P3AKB OF BONDOWOSO REGENCY - Muhammad Sohib; Devi Hardianti Rukmana (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The focus of this study is: (1) how the SIBAPER system is implemented in recording inventory goods at DINSOS P3AKB of Bondowoso Regency; (2) how the Inventory Goods System improves the effectiveness of financial report recording at DINSOS P3AKB of Bondowoso Regency; and (3) the constraints encountered in implementing the Inventory Goods System at DINSOS P3AKB of Bondowoso Regency. The objectives of the study are directed to: (1) identify how the Inventory Goods System SIBAPER  is implemented at DINSOS P3AKB of Bondowoso Regency; (2) examine how the Inventory Goods System SIBAPER enhances the effectiveness of financial report recording at DINSOS P3AKB of Bondowoso Regency; and (3) identify the constraints in the implementation of the Inventory Goods System SIBAPER at DINSOS P3AKB of Bondowoso Regency. This research employs a qualitative approach using a descriptive method. Data were collected through in-depth interviews, field observations, and document analysis. The research informants consisted of system operators, financial staff, and the head of the goods management sub-division, who are directly involved in inventory management. The conclusions of this study reveal that the implementation of SIBAPER has a positive impact in the form of improved accuracy, efficiency, and transparency in inventory recording. These conditions contribute to the preparation of more accountable financial reports. However, there are still obstacles, including limited user competencies, a lack of technical training, and resistance to the adoption of new technologies, which reduce the overall effectiveness of the system.